2011
DOI: 10.1007/s11136-011-9922-7
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and its impact on the health-related quality of life in children and adolescents: results from the European KIDSCREEN survey

Abstract: This is one of the first studies comparing the impact of HRQoL at European level using a generic and internationally valid HRQoL instrument, and the results show that, irrespective of national background, overweight children and adolescents are significantly impaired on their HRQoL, in particular on the physical well-being and the self-perception domain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
93
3
15

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(129 citation statements)
references
References 47 publications
18
93
3
15
Order By: Relevance
“…Moreover, obese youth frequently face social exclusion and are less likely than their normal-weight peers to be nominated as friends [9,10]. Therefore, it is not surprising that the psychosocial adjustment of obese youth, particularly their quality of life (QOL) [4,9,[11][12][13][14] and psychological functioning [6,15,16], is frequently compromised.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, obese youth frequently face social exclusion and are less likely than their normal-weight peers to be nominated as friends [9,10]. Therefore, it is not surprising that the psychosocial adjustment of obese youth, particularly their quality of life (QOL) [4,9,[11][12][13][14] and psychological functioning [6,15,16], is frequently compromised.…”
Section: Introductionmentioning
confidence: 99%
“…When compared with normal-weight youth, youth with obesity tend to report significantly worse QOL in several domains [12,[17][18][19]. Some studies have even found that the QOL of treatment-seeking obese youth is similar to that of youth with cancer [18] and is lower than that of youth with other chronic conditions [20].…”
Section: Introductionmentioning
confidence: 99%
“…La obesidad durante la niñez y adolescencia se ha asociado con un mayor riesgo de desarrollar diabetes tipo 2, hipertensión arterial, enfermedad coronaria 2 , síndrome metabólico 3 , entre otros. Por otro lado, la calidad de vida de los niños/as afectados podría verse limitada particularmente en las áreas relacionadas con el bienestar físico y psicosocial 4,5 .…”
Section: Introductionunclassified
“…This finding was demonstrated in a study with a sample of 10 European countries. The results showed that overweight young people present lower scores in physical well-being, mood and emotions, self-perception, social support and peer relations, social acceptance, and bullying dimensions of the KIDScrEEN-52 questionnaire [22]. In Australians there is an inverse association between body mass index and HrQOL scores in the physical health, psychosocial health, emotional functioning, and social functioning dimensions of the PedsQL questionnaire [12].…”
Section: Discussionmentioning
confidence: 96%